Evaluation of Toxocara cati Excretory–Secretory Larval Antigens in Serodiagnosis of Human Toxocariasis. Issue 3 (1st April 2015) - Zibaei, Mohammad; Sadjjadi, Seyed Mahmoud; Sarkari, Bahador; Uga, Shoji
Abstract : Background: Toxocariasis is the clinical term that is applied to infection in the human host with Toxocara species larvae. Serological tests are important tools for the diagnosis of toxocariasis. The aim of this study was to evaluate the excretory–secretory (ES) antigens of T. cati larvae using enzyme‐linked immunosorbent assay (ELISA) and also Western blotting for serodiagnosis of human toxocariasis. Method: The ES antigens were prepared from T. cati third‐stage larvae. Serum samples were obtained from 33 confirmed cases of toxocariasis, 35 patients infected with other parasitic diseases, and 30 from healthy individuals tested with ELISA and immunoblotting. Results: The ELISA showed appropriate performance in term of specificity (96.7%) and sensitivity (97.0%). Electrophoretic analysis of T. cati ES antigens revealed a range of 20‐ to 150‐kDa fractions. The highest sensitivity was achieved with 42‐ and 50‐kDa fractions. Conclusion: The ELISA analyses using T. cati ES antigens demonstrated good sensitivity and specificity compared to T. canis ES as antigens for diagnosis of human toxocariasis. Accordingly, application of Western blotting, based on 42‐ and 50‐kDa fractions of ES antigens, can be recommended for the accurate diagnosis of toxocariasis.